Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Guru SMA Muhammadiyah di Kabupaten Kebumen - Eliyanto Eliyanto (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This research aimed to explain the influence of work motivation and work environment on teacher performance of Muhammadiyah High School in Kebumen Regency. This study was quantitative (explanatory research). The population and sample of this research was all of teacher of Muhammadiyah High School in Kebumen Regency, that is 55 people. The data were collected using a questionaire, and analyzed using descriptive analysis, multiple liniear regression, t table, and F change. This research produces conclusions that the work motivation is significantly influence the teacher performance of the Muhammadiyah High School in Kebumen Regency, indicated by the t significant value of 0.000 smaller than α = 0.05 (0.000 <0.05) with the regression coefficient of 0.699. Work environment has a significant effect on the teacher performance of Muhammadiyah High School in Kebumen Regency, indicated by the t significant value of 0,014 less than α = 0.05 (0.014 <0.05) with the regression coefficient of 0.248. Work motivation and the work environment is simultaneously significant effecting the teacher performance of Muhammadiyah High School in Kebumen Regency, indicated by F significant value of 0.000 smaller than α = 0.05 (0.000 <0.05) and were able to contribute to the teacher performance variables of 0.726 or 72,6%, however the remaining 27,6% is influenced by other variables that are not examined in this research.